Designing Effective Macroprudential Stress Tests : Progress So Far and the Way Forward - Demekas, Dimitri (IMF Working Papers; Working Paper, 2015)
Giving stress tests a macroprudential perspective requires (i) incorporating general equilibrium dimensions, so that the outcome of the test depends not only on the size of the shock and the buffers of individual institutions but also on their behavioral responses and their interactions with each other and with other economic agents; and (ii) focusing on the resilience of the system as a whole. Progress has been made toward the first goal: several models are now available that attempt to integrate solvency, liquidity, and other sources of risk and to capture some behavioral responses and feedback effects. But building models that measure correctly systemic risk and the contribution of individual institutions to it while, at the same time, relating the results to the established regulatory framework has proved more difficult. Looking forward, making macroprudential stress tests more effective would entail using a variety of analytical approaches and scenarios, integrating non-bank financial entities, and exploring the use of agent-based models. As well, macroprudential stress tests should not be used in isolation but be treated as complements to other tools and-crucially-be combined with microprudential perspectives.